Social Workers' Perceptions of Structural Inequality and Immigrant Threat: Results From a National Survey. (3rd July 2022) - Park, Yoosun; Torres, Maria; Bhuyan, Rupaleem; Ao, Jixia; Graves, Lucy; Rundle, Andrew
ABSTRACT: As part of a national survey on social workers' attitudes toward immigrants and immigration ( N =4, 499), we collected information on respondents' perceptions of immigrants as threats and respondents' views on structural inequality as it pertains to immigrants' opportunities for success. Contrary to the Council on Social Work Education's Educational Policy and Accreditation Standards stating the need for social workers to understand the existence and functioning of structural forces of inequality, nearly a third of our respondents denied that immigrants are disadvantaged compared to U.S.-born citizens, and more than a third denied that disadvantage is related to race, ethnicity, or national origin. Those who denied disadvantage were more likely than those who did not to see immigrants as threats. We provide interpretations for these findings and offer some recommendations for social work research and education geared toward deepening practitioners' knowledge of the structural barriers faced by immigrants.